Programma: 2 december Little Bob Story; 3 december Otis Waygood Band; 5 december Whizz Guy, Flying Spiderz, Eater; 9 december Greg Kihn Band; 11 december The Cimarons
Programma: 2 december Little Bob Story; 3 december Otis Waygood Band; 5 december Whizz Guy, Flying Spiderz, Eater; 9 december Greg Kihn Band; 11 december The Cimarons.